2018
DOI: 10.1080/01635581.2018.1504092
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia: Identification by Clinical Assessment versus International Consensus Criteria in Patients with Metastatic Colorectal Cancer

Abstract: Background: Cancer cachexia is associated with poorer outcomes and is often diagnosed by the Fearon criteria. Oncologists clinically identify cachexia based on a patient's presentation. In this study agreement between these identification methods was evaluated and associations with outcomes were studied in patients with metastatic colorectal cancer. Methods: Fearon criteria comprised weight loss >5% OR weight loss >2% with either BMI <20 kg/m 2 or sarcopenia (determined by CT-imaging). Clinical assessment by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…To date, CC classification work has centered on validation or refinement of the proposed diagnostic criteria in research settings. 2,5,29 Only one study 17 has evaluated the agreement between CC by clinical presentation and the ICC stages. Clinical assessment comprised an oncologist's opinion based on (undefined) clinical presentation (ie, cachectic vs not cachectic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, CC classification work has centered on validation or refinement of the proposed diagnostic criteria in research settings. 2,5,29 Only one study 17 has evaluated the agreement between CC by clinical presentation and the ICC stages. Clinical assessment comprised an oncologist's opinion based on (undefined) clinical presentation (ie, cachectic vs not cachectic).…”
Section: Discussionmentioning
confidence: 99%
“…14 Prior studies 15,16 have also demonstrated that oncology nurses are not appropriately educated to recognize and manage CC. Van der Werf et al 17 found weak agreement between an oncologist's CC assessment by clinical presentation and the ICC classification. Oncologists may lack confidence in identifying malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…CCM contains factors that inhibit both myoblast proliferation and myogenic differentiation [ 39 ]. The in vitro and in vivo experiments in this study utilized the CT26 colon carcinoma cell line because cancer cachexia is commonly associated with this tumor type [ 65 ]. Cancer cachexia is a common complication of lung, breast, and pancreatic carcinoma [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical definition of CAC by Fearon criteria includes the following characteristics: weight loss > 5% or weight loss > 2% and a BMI < 20 kg/m 2 or sarcopenia [ 46 ]. In this study, 15- to 24-week-old Apc Min/+ mice with weight loss > 15%, as well as skeletal muscle (gastrocnemius and soleus) loss, and certain other symptoms such as anemia, were considered as the characteristics of CAC.…”
Section: Discussionmentioning
confidence: 99%